The Short-Term follow up of Changes in Serum Leptin, Ghrelin, and HBA1c after Laparoscopic Roux-en-Y Gastric Bypass (LRYGB) Operation - Safauldeen Salim (Journal of Global Pharma Technology, 2017)
Introduction: Morbid obesity is connected with various health related problems, so treating obesity is an essential clinical concern. Swedish subject obesity study with 10 years follow up showed that surgical option is far better than conservative approach. Aim To assess changes in adipose hormones and HbA1c in obese patients after Laparoscopic Roux-en-Y Gastric Bypass (LRYGB). Materials and Methods the study was conducted on 25 subjects (14 females and 11 males), age 32±6, with BMI 52.01 ± 3.5 Kg/m² underwent LRYGB during the period from June 2015 to the end of February 2016. Fasting blood glucose (FBG), HbA1c, serum level of Lept in and Ghrel in were measured before the operation, 2, 4 and 6 months after LRYGB procedure. Results At 6 months point following LRYGB, a significant reduction in body weight and BMI (p< 0.001) was reported. The mean weight of the participants decreased to 82.7 Kg, mean BMI decreased to 31.1 Kg/m2 and mean fat % declined to 35.55%. The mean loss in the EBL percent was 77.3 % and %Excess Weight Loss (EWL) was 39.9%. There was significant reduction in FBG, HbA1c and serum Leptin level (p< 0.001) with significant increase in serum Ghrelin level (p<0.001).Conclusions LRYGB produced a rapid and significant weight loss and improvement in glucose homeostasis within six months after surgery. It had resulted in significant changes in the level of leptin and ghrel in. There were differences between males and females after 6 months of follow-up.Keywords: Obesity, Bariatric surgery, Ghrelin, Leptin, Follow-up. Fasting blood Sugar, Excess weight Loss.